Students’ Difficulties in Translating English Text at Tadulako University: A Qualitative Study - Miftahul Jannah; Jamiluddin Jamiluddin; Afrillia Anggreni; Hasna Hasna (Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the difficulties experienced by students in translating English texts at Tadulako University and identifies the factors influencing these difficulties. The research employed a descriptive qualitative method involving fifth-semester students of the English Education Study Program who had completed a translation course. Data were collected through semi-structured interviews, questionnaires, and analysis of students’ translation assignments. The findings show that students encounter several major problems in translation, including limited vocabulary mastery, grammatical errors, and difficulty interpreting homonyms. Vocabulary limitation was identified as the most dominant challenge because students often struggled to understand word meanings and determine appropriate equivalents in the target language. In addition, differences in grammatical structures, especially the use of the simple past tense, frequently caused inaccurate sentence construction. Students also faced difficulties in identifying the correct meaning of homonyms based on context. Furthermore, the study reveals that affective factors, such as boredom and low motivation, significantly contribute to students’ translation problems. These findings suggest that translation difficulties are influenced not only by linguistic competence but also by students’ attitudes toward learning. Therefore, translation teaching should emphasize vocabulary development, contextual understanding, and more engaging instructional strategies to improve students’ translation abilities effectively.